Pengaruh Model Pembelajaran Langsung terhadap Sikap Ilmiah dan Hasil Belajar Kognitif Siswa - Iswantoro, Lisna; Fajar, Chandra (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
The purpose of this study was to determine the effect of the direct learning model on scientific attitudes and cognitive learning outcomes for grade VII students of SMP Negeri 2 Trimurjo in the 2018/2019 academic year. This research is a quasi-experimental research with Pretest Posttest Control Group Design. The population in this study were all students of class VII SMP Negeri 2 Trimurjo with the research sample consisting of two classes, namely class VII A as many as 28 students as the experimental class and class VII B as many as 28 students as the control class taken by random sampling technique. Based on the results of the study, it is known that both classes experienced an increase in scientific attitude. The percentage of scientific attitude in the experimental class and the control class were 74.51% and 67.65%, respectively, and increased to 86.27% and 72.55%, respectively. Students' cognitive learning outcomes also increased. The average pretest scores of the experimental class and the control class were 38.92 and 45.53, respectively, increasing to 52.5 and 71.96 at the posttest. This data was then analyzed using t-test analysis (t-test) at a significant level of 5%, the t-value was 7.652, the value was greater than the t-table value of 1.674. This shows that there is an influence of the direct learning model on scientific attitudes and cognitive learning outcomes for grade VII students of SMP Negeri 2 Trimurjo in the 2018/2019 school year.